The Role of Serum Cytokines in the Pathogenesis of Hepatic Osteodystrophy in Male Cirrhotic Patients. (14th October 2012) - Soylu, Ali Riza; Tuglu, Cengiz; Arikan, Ender; Yetisyigit, Tarkan; Kunduracılar, Hakan; Koker, Ibrahim Hakki; Unsal, Gulbin; Tezel, Ahmet Huseyin; Umit, Hasan; Berkarda, Sakir
Abstract : Objective . In this study, we aimed to investigate the possible role of serum cytokines in the development of hepatic osteodystrophy. Matherial and Methods . 44 consecutive male cirrhotic patients (17 alcoholic, 20 hepatitis B, 7 hepatitis C), 15 age- and sex-matched chronic alcoholics without liver disease, and 17 age- and sex-matched healthy controls were included in the study during one year period. Bone mineral density was measured by dual X-ray absorptiometry in the lumbar vertebrate and femoral neck. Serum interleukin levels were measured by ELISA method. Results . Although osteopenia frequency between our cirrhotic patients was 20%, there was no difference in T-scores among the controls and other groups. Serum interleukin-1, interleukin-8, and tumor necrosis factor-alpha levels were not different between all groups. Serum interleukin-2 and interleukin-6 levels were higher in the cirrhotics than controls (P < 0.001 ). However, there were no significant difference between osteopenic and nonosteopenic cirrhotics. Conclusion . According to the results of the study in this small population of 44 male cirrhotic patients, frequency of hepatic osteopenia is small and serum interleukins 1, 2, 6, 8, and tumor necrosis factor-alpha may not play a role in the pathogenesis of hepatic osteodystrophy. Further studies in which large number of patients involved are necessary in this field.